Precursor-route ZnO films from a mixed casting solvent for high performance aqueous electrolyte-gated transistors. Issue 46 (9th November 2015) - Althagafi, Talal M.; Algarni, Saud A.; Al Naim, Abdullah; Mazher, Javed; Grell, Martin
Abstract : We significantly improved the performance of precursor-route semiconducting zinc oxide (ZnO) films in electrolyte-gated thin film transistors (TFTs). Abstract : We significantly improved the performance of precursor-route semiconducting zinc oxide (ZnO) films in electrolyte-gated thin film transistors (TFTs). We find that the organic precursor to ZnO, zinc acetate (ZnAc), dissolves more readily in a 1 : 1 mixture of ethanol (EtOH) and acetone than in pure EtOH, pure acetone, or pure isopropanol. XPS and SEM characterisation show improved morphology of ZnO films converted from a mixed solvent cast ZnAc precursor compared to the EtOH cast precursor. When gated with a biocompatible electrolyte, phosphate buffered saline (PBS), ZnO thin film transistors (TFTs) derived from mixed solvent cast ZnAc give 4 times larger field effect current than similar films derived from ZnAc cast from pure EtOH. The sheet resistance at V G = V D = 1 V is 30 kΩ □ −1, lower than for any organic TFT, and lower than for any electrolyte-gated ZnO TFT reported to date.